2010
DOI: 10.1016/j.chom.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A Biphasic Innate Immune MAPK Response Discriminates between the Yeast and Hyphal Forms of Candida albicans in Epithelial Cells

Abstract: SummaryDiscriminating between commensal and pathogenic states of opportunistic pathogens is critical for host mucosal defense and homeostasis. The opportunistic human fungal pathogen Candida albicans is also a constituent of the normal oral flora and grows either as yeasts or hyphae. We demonstrate that oral epithelial cells orchestrate an innate response to C. albicans via NF-κB and a biphasic MAPK response. Activation of NF-κB and the first MAPK phase, constituting c-Jun activation, is independent of morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
478
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(519 citation statements)
references
References 41 publications
32
478
1
3
Order By: Relevance
“…Activation of NF-kB and c-Jun Yes Yes [58] Activation of c-Fos and MKP1 No Yes, dose dependent [58] Proinflammatory cytokines No Yes, dose dependent [58] Review Candida albicans dimorphism as a therapeutic target competition assays, Keppler-Ross et al observed higher uptake of yeast than hyphae by macrophages [64]. Thus, more research is needed to fully elucidate the role of fungal morphology in the interaction with macrophages.…”
Section: Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of NF-kB and c-Jun Yes Yes [58] Activation of c-Fos and MKP1 No Yes, dose dependent [58] Proinflammatory cytokines No Yes, dose dependent [58] Review Candida albicans dimorphism as a therapeutic target competition assays, Keppler-Ross et al observed higher uptake of yeast than hyphae by macrophages [64]. Thus, more research is needed to fully elucidate the role of fungal morphology in the interaction with macrophages.…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…So how do epithelial cells discriminate between C. albicans colonization and infection? Recently, Moyes et al have begun to shed light on the molecular mechanisms for this discriminatory process, and their data indicates that both the morphological form of C. albicans and the fungal burden are crucial [58]. Oral epithelial cells appear to orchestrate responses to C. albicans via NF-kB and a biphasic MAPK signaling mechanism.…”
Section: Recognition By and Interaction With The Immune System: Yeast Vmentioning
confidence: 99%
“…17 MAPK pathway is revealed to identify the invasive C. albicans, while NF-kB pathway is in charge of anti-fungal responses. 17 The activation of the pathways would lead to series of biological effects, and the effects can be divided into 2 categories. One is to activate weak but direct anti-fungal defense by secreting antimicrobial peptides (such as b-defensins and LL-37).…”
Section: Prrs Of Epithelial Cellsmentioning
confidence: 99%
“…MAPK/MKP1/c-Fos activation may be critical for identifying and responding to the pathogenic switch of commensal microbes. 17 An open question is what exact PAMPs on different forms of C. albicans are presented to immune cells. To date, this question is partly answered.…”
Section: Differential Recognition Of Yeasts and Hyphaementioning
confidence: 99%
See 1 more Smart Citation